3.4 GHz strip-type thickness shear mode solidly-mounted bulk acoustic wave resonator using X-cut LiTaO3. (1st July 2022) - Kadota, Michio; Ishii, Yoshimi; Tanaka, Shuji
Abstract: This paper describes a high-frequency bulk acoustic wave resonator (BAWR) with a solidly-mounted (SM) structure using single crystal LiTaO3 (LT) thin plates. A Bragg reflector solidly supports the LT thin plate, which is fragile if self-suspended. The two kinds of BAWRs use a strip-type thickness shear mode in 0.56 μ m thick X37°Y LT and X127°Y LT. The Bragg reflector is made of 5 pairs of Al and Ta films, i.e. 10 layers in total. The X37°Y LT SM structure BAWRs exhibited a resonance frequency ( f r ) of 3.250 GHz, an anti-resonance frequency ( f a ) of 3.463 GHz, a bandwidth (BW) of 6.6%, and an impedance ( Z ) ratio of 48 dB. The X127°Y LT BAWR has a similar characteristic with f r of 3.153 GHz, f a of 3.367 GHz, a BW of 6.8%, and a Z ratio of 46 dB. The X37°Y LT BAWR showed an advantage of 2 dB compared with the X127°Y LT one. The Al film acts as a low acoustic impedance film, but an acoustic impedance layer combination of Al and Ta films is not suitable and that of SiO2 and W films suitable among the four combinations, Al/Ta. SiO2 /Ta, Al/W, and SiO2 /W films. Although the acoustic impedance layer combination, the acoustic film quality, the structure, electrode design, and fabrication process of the fabricated BAWRs were not optimized yet, this result suggests the high potential of this device.